2017
DOI: 10.3390/ma10040399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tungsten Addition on the Microstructure and Corrosion Resistance of Fe-3.5B Alloy in Liquid Zinc

Abstract: The effects of tungsten addition on the microstructure and corrosion resistance of Fe-3.5B alloys in a liquid zinc bath at 520 °C were investigated by means of scanning electron microscopy, X-ray diffraction and electron probe micro-analysis. The microstructure evolution in different alloys is analyzed and discussed using an extrapolated Fe-B-W ternary phase diagram. Experimental results show that there are three kinds of borides, the reticular (Fe, W)2B, the rod-like (Fe, W)3B and flower-like FeWB. The additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The corrosion tests were executed in a graphite crucible placed in a vertical resistance furnace with the temperature maintained at 520 ± 3 °C for 24, 48, 72, 96, and 120 h. Then, these specimens were removed from the molten zinc and cooled quickly by water quenching to preserve the microstructure at that temperature. The average corrosion depth and corrosion rate of the tested specimen were calculated with the following Equations (1) and (2) [ 18 , 19 , 20 , 21 ]: H = (a − b)/2 R = h/t where h is the average corrosion depth (μm), a is the original thickness (μm), b is the final thickness (μm), R is the corrosion rate (μm·h −1 ), and t is the corrosion time (h).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion tests were executed in a graphite crucible placed in a vertical resistance furnace with the temperature maintained at 520 ± 3 °C for 24, 48, 72, 96, and 120 h. Then, these specimens were removed from the molten zinc and cooled quickly by water quenching to preserve the microstructure at that temperature. The average corrosion depth and corrosion rate of the tested specimen were calculated with the following Equations (1) and (2) [ 18 , 19 , 20 , 21 ]: H = (a − b)/2 R = h/t where h is the average corrosion depth (μm), a is the original thickness (μm), b is the final thickness (μm), R is the corrosion rate (μm·h −1 ), and t is the corrosion time (h).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of Cr, Mn, W, Mo, Ti, rare earth, and other elements on the fracture toughness and hardness of Fe 2 B in Fe-B-C cast alloy have been investigated [ 16 , 17 ], while the effect of Cr, Ni, W, Mo, and other elements on the corrosion resistance of Fe-B alloys in molten zinc baths was reported upon [ 18 , 19 , 20 , 21 ]. Recently, Jian et al [ 16 ] investigated the effect of Mn addition on the microstructure, mechanical properties, and wear behavior of an Fe-3.0B alloy, finding that proper Mn addition could improve the toughness of Fe 2 B. Liu et al [ 20 ] reported that adding 11 wt.% W to the Fe-3.5B alloy could significantly increase its corrosion resistance to molten zinc by the improvement of boride stability and through the grain refining of eutectic borides. However, the brittle characteristics of the boride phase and the preferential corrosion of the α-Fe phase remain dominant reasons for corrosion failure, which cause difficulties in meeting (CGL) industry requirements.…”
Section: Introductionmentioning
confidence: 99%
“…As we can see from the figures 11(a) and (c) that there are micro-cracks propagated from the crystalline grain boundary to intragranular. It is mainly caused by the local stress concentration and the existence of brittle inter-crystalline carbides [31][32][33][34][35]. The microcracks will continue to propagate and eventually result in grain breakage.…”
Section: Worn Surface Layer's Microstructurementioning
confidence: 99%
“…However, brittleness and cracks form easily and expand, which lead to the failure of FeB in liquid zinc. Results showed that corrosion resistance of FeB alloy can be enhanced by alloying with Mo or W; however, it was still highly brittle [18,19]. The brittleness of FeB can be improved by using Co as the bonding phase, but it is easily eroded by liquid zinc, which is the primary reason for failure [20].…”
Section: Introductionmentioning
confidence: 99%